MEMBANGUN KESADARAN UMKM TERHADAP POTENSI PENJUALAN MELALUI ONLINE SHOP DI DESA BANYURASA, KECAMATAN SUKAHENING, KABUPATEN TASIKMALAYA - Alrisqi, Narisa Nur; Effendi, Tasya; Julimah, Ratna; Sopiatunnisa, Neneng; Sholihat, Lisna Mardiana (Jurnal Pengabdian Masyarakat Polmanbabel, 2025)
MSME players in Banyurasa Village, Sukahening Subdistrict, face constraints in the lack of utilization of digital platforms for marketing, limiting competitiveness and market expansion. This service program aims to improve the digital literacy and skills of MSME actors through training in online shop management and digital marketing. The research method used is descriptive qualitative, with data collection techniques through interviews, observation, and documentation. The activity stages include initial data collection to understand business conditions, field surveys to identify challenges and potentials, and a seminar themed "Online Shop" which provides practical training on online shop operations, digital marketing strategies, and social media management. The results showed significant improvements in the understanding and skills of MSME players, especially in using social media for promotion, understanding the importance of branding, and utilizing digital platforms to expand markets. In addition, participants showed enthusiasm in applying the new knowledge to grow their businesses. In conclusion, this program succeeded in increasing the capacity of MSME players in facing the challenges of the digital era and had a positive impact on the competitiveness and income potential of local businesses. Continued support from various parties is needed to ensure the sustainability of the positive impact of this program.